Kerja Sama Taiwan-Amerika Serikat Dalam Menghadapi Ancaman China Periode 2016-2020 - Hesti Rosdiana; Aisyah Saharani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Taiwan is considered as a renegade province by China. Taiwan, however, disagrees and trying to raise public awareness that it is a sovereign nation. Tensions have increased since the election of Tsai Ing-wen as president of Taiwan in 2016. China's military activity has increased since then, marked by warplane flights around Taiwan to military exercises in the border area. The final results of this study show that Taiwan sees China's increased military activity as a threat and tries to balance the threat through military cooperation and diplomacy. Taiwan made an alliance with the US through the US-ROC Mutual Defense Treaty which later became the Taiwan Relations Act in 1979 due to the birth of the One China Policy. Taiwan tried to maintain the Status Quo with China while gathering support and recognition from other countries through military cooperation and diplomacy.